KETERKAITAN ANTARA BIM 4D DAN PENGENDALIAN WAKTU PELAKSANAAN PADA PEMBANGUNAN PERUMAHAN (Studi Kasus: Perumahan Alya Residence) - Prasetyo, Reza; Andri, Andri; Salam, Muhammad; Priskhal, Priskhal; Nuhun, Ridwansyah; Soeparyanto, Try Sugiyarto; Welendo, La (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2024)
The application of 4D Building Information Modeling (BIM) in the construction industry has introduced a new paradigm in project management, especially in the context of housing development. Project cost control is a critical factor that influences the success and profitability of construction projects. This research aims to analyze the relationship between 4D BIM and cost control in housing construction. This research methodology uses a qualitative approach with case studies. The Alya Residence housing development is a reference in the use of this technology. Data was collected through in-depth interviews with construction professionals involved in housing development projects. In addition, data is also collected from project documentation, including initial and final cost estimates, as well as cost evaluations throughout the project cycle. The research results show that 4D BIM integration has a positive impact on controlling housing development project costs. 4D visualization allows project teams to identify potential cost deviations early, enabling timely corrective action